2005
DOI: 10.1038/oby.2005.184
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Indices and the Incidence of Hypertension: A Comparative Analysis

Abstract: Research Methods and Procedures:Participants were 592 individuals free of hypertension, selected at random from the community. In the baseline evaluation, they were submitted to completed measures of demographics, anthropometrics, blood pressure, and other risk factors for hypertension. Incident hypertension was defined by blood pressure equal or higher than 140/90 mm Hg or use of blood pressure-lowering drugs. Results: During a mean follow-up time of 5.6 Ϯ 1.1 years, 127 developed hypertension. The hazard rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 9 publications
4
77
1
4
Order By: Relevance
“…The high percentage of smokers observed in the sample is also mentioned in other studies with hypertensive individuals 13,14 . Paradoxically, Boing and Boing 17 found lower values (18.2%) for patients registered at the HyperDay Program.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The high percentage of smokers observed in the sample is also mentioned in other studies with hypertensive individuals 13,14 . Paradoxically, Boing and Boing 17 found lower values (18.2%) for patients registered at the HyperDay Program.…”
Section: Discussionmentioning
confidence: 48%
“…However, the male sex presented a higher risk for reduced GF in the two groups assessed in the study, although there was no significant association. The predominance of the female sex, a common finding in several studies with hypertensive populations [12][13][14][15] can be attributed to the fact that women more frequently seek systematic medical attention 16 and to the higher prevalence of these patients registered at the HyperDia Program 17 . Another possible explanation is that women present a higher frequency of AH from the sixth decade on 18 , and a higher life expectancy at birth (76.5 years) when compared to men 16 .…”
Section: Discussionmentioning
confidence: 99%
“…2 In both black and white populations, hypertension is frequently associated with centripetal obesity, insulin resistance, and dyslipidemia. [3][4][5] This constellation of risk factors has been termed the metabolic syndrome and is associated with increased cardiovascular disease morbidity and mortality. 6,7 Based on an earlier study of the records of 35 000 consecutive autopsies, an increased prevalence of adrenal cortical adenomas and hyperplasia has been observed in association with essential hypertension, particularly in younger and middle-aged black adults.…”
mentioning
confidence: 99%
“…We have previously demonstrated in this cohort that waist circumference was more consistently associated with the incidence of hypertension than the BMI, 5 and that the correction of waist by the stature of the individual increased its predictive performance. 10 A consistent positive association between alcohol intake and blood pressure has been established in populations throughout the world. 11 In the baseline data of our study, we identified an association between alcohol consumption and blood pressure that was influenced by the time since the last alcohol intake.…”
mentioning
confidence: 90%